Chinese expert consensus on prevention and control interventions for older adults with physical functional impairment (2022). Issue 1 (27th February 2023) - Wu, Jianqing; Chen, Bo; Mao, Yongjun; Li, Siyuan; Zhao, Weihong; Meng, Dianhuai; Hu, Song; Wang, Jianye; Yu, Pulin; Zhang, Cuntai; Wu, Jinhui; ,
Abstract: Older adults are at high risk for functional impairment, which is closely related to sarcopenia, falls, and frailty. This seriously affects their quality of life and health, and places a heavy burden on society and families. Although domestic and foreign sports recommendations and prevention and control guidelines/expert consensus have been issued for healthy older adults and functional impairment‐related diseases, there is no guidance on prevention and control interventions for older adults with physical functional impairment. In China, there is insufficient understanding of the importance of prevention and control interventions for functional impairment in older adults, and there are many drawbacks, such as unstandardized diagnosis and treatment, and relatively simple intervention methods. Therefore, the consensus expert group formulated a consensus based on domestic and foreign guidelines related to functional impairment in older adults to provide guidance for Chinese medical professionals working in the field of geriatrics. Abstract : The risk factors for functional impairment are complex, including age, gender, chronic diseases, daily behavior, psychological factors, socioeconomic conditions, and many others. Elderly adults suspected of functional impairment should be intervened after being assessed and diagnosed of functional impairment. It is recommended to adopt a multidisciplinary team cooperation model, educate patients, and individualized exercise programs.